“Evaluación de siete cultivares de lechuga (Lactuca Sativa) en el barrio 20 de diciembre, Pujilí, Cotopaxi 2023” - Sangovalin Copara, Liliana Giomayra (2023)
The research was carried out in order to reduce monoculture and thus provide useful information to small producers in the sector, the adaptability of seven lettuce cultivars (Lactuca sativa) in the 20 de Diciembre neighborhood, Pujilí, Cotopaxi, was evaluated. A DBCA (Completely Random Block Design) was carried out, consisting of 3 repetitions and 7 treatments including the controls, with a total of 21 experimental units, the cultivars under study were: AEX 132-4690, Imma, Salinas 3016, GVS29205, Salinas 3018, Patagonia, Waltz, the results in percentage of taking (98,89%), height of the plant that was taken during the days: 15 days (3,04 cm), 30 days (6,59 cm), 45 days (11,5 cm), 60 days (16,5 cm), rosette formation (21,33 days), cabbage formation (51,67 days), leaf anthocyanin coloration on scale (5) absent , major leaf vein at scale (3) intermediate, leaf texture at scale (5) crisp, leaf shape at scale (4) broad rhombic, pest and disease tolerance at scale (5) no symptoms, cabbage color on scale (5) light green, cabbage shape on scale (5) round, cabbage solidity on scale (5) very solid, harvest (70 days), cabbage equatorial diameter (108,35mm ), cabbage weight (456,13gr) and yield (2340kg/ha) these results were presented in the cultivar AEX132-4090, the same one that adapted to the conditions of Barrio 20 de Diciembre, Pujilí canton.